An mTOR and VEGFR inhibitor combination arrests a doxorubicin resistant lung metastatic osteosarcoma in a PDOX mouse model - Oshiro, Hiromichi (Sci Rep, 2021)
In order to identify more effective therapy for recalcitrant osteosarcoma, we evaluated the efficacy of an mTOR-VEGFR inhibitor combination on tumor growth in a unique osteosarcoma patient-derived orthotopic xenograft (PDOX) mouse model derived from the lung metastasis of an osteosarcoma patient who failed doxorubicin therapy. We also determined the efficacy of this inhibitor combination on angiogenesis using an in vivo Gelfoam fluorescence angiogenesis mouse model implanted with osteosarcoma patient-derived cells (OS-PDCs). PDOX models were randomly divided into five groups of seven nude mice. Group 1, control; Group 2, doxorubicin (DOX); Group 3, everolimus (EVE, an mTOR and VEGF inhibitor); Group 4, pazopanib (PAZ, a VEGFR inhibitor); Group 5, EVE-PAZ combination. Tumor volume and body weight were monitored 2 times a week. The in vivo Gelfoam fluorescence angiogenesis assay was performed with implanted OS-PDCs. The nude mice with implanted Gelfoam and OSPDCs also were divided into the four therapeutic groups and vessel length was monitored once a week. The EVE-PAZ combination suppressed tumor growth in the osteosarcoma PDOX model and decreased the vessel length ratio in the in vivo Gelfoam fluorescent angiogenesis model, compared with all other groups (p < 0.05). There was no significant body-weight loss in any group. Only the EVE-PAZ combination caused tumor necrosis. The present study demonstrates that a combination of an mTOR-VEGF inhibitor and a VEGFR inhibitor was effective for a DOX-resistant lung-metastatic osteosarcoma PDOX mouse model, at least in part due to strong anti-angiogenesis efficacy of the combination.